2008
DOI: 10.1111/j.1745-9133.2008.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a National Estimate of Police Use of Nonlethal Force*

Abstract: Research SummaryDespite frequent calls for national data on police use of force, the literature is dominated by unrepresentative samples from a small number of primarily urban jurisdictions, inconsistent definitions of force, and differing universes for the computation of rates. Among 36 publications that report on the amount of nonlethal force used by the police, rates vary from 0.1% to 31.8%. To improve our ability to estimate the amount of nonlethal force in the United States, we employ data from two source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 38 publications
(52 reference statements)
6
105
0
Order By: Relevance
“…When force is used, it is usually in response to one of the following behaviors identified in the literature: resisting officer requests, acting disrespectful toward officers, attacking officers, possessing a weapon, or running away from the police, but not mental illness (cf. Garner and Maxwell, ; Hickman et al, ; Jacobs and O'Brien, ; Kaminski, Digiovanni, and Downs, ; Terrill and Mastrofski, ). Given the low levels of force typically used by police officers, the subsequent injuries that result from all encounters are minor, described mostly as abrasions and bruises (Alpert and Dunham, ).…”
Section: Police and People With Mental Illnessesmentioning
confidence: 99%
“…When force is used, it is usually in response to one of the following behaviors identified in the literature: resisting officer requests, acting disrespectful toward officers, attacking officers, possessing a weapon, or running away from the police, but not mental illness (cf. Garner and Maxwell, ; Hickman et al, ; Jacobs and O'Brien, ; Kaminski, Digiovanni, and Downs, ; Terrill and Mastrofski, ). Given the low levels of force typically used by police officers, the subsequent injuries that result from all encounters are minor, described mostly as abrasions and bruises (Alpert and Dunham, ).…”
Section: Police and People With Mental Illnessesmentioning
confidence: 99%
“…Second, some of the explanation may be tied to the infrequency of the event. Data consistently show that police use of force occurs in less than 2% of police–citizen encounters and that the force most commonly used by police is minor (Hickman, Piquero, and Garner, ). Use of deadly force represents a tiny percentage of an already rare event.…”
Section: Potential Explanations For the Failure To Establish A Nationmentioning
confidence: 99%
“…A recent literature review (Hickman et al 2008 ) identifi ed 36 studies reporting an incident-based rate of police use of force and found that the majority of studies were based on data from a single jurisdiction and the methods were quite diverse (including arrest reports, household surveys, independent observations, police surveys, suspect surveys, and offi cial use of force forms), as were the units of analysis (arrests, contacts, citizen encounters, disputes, police stops, potentially violent mobilizations, suspect encounters, and calls for service ). Somewhat unsurprisingly, across 36 studies reporting on the amount of nonlethal force used by the police, rates varied from about a tenth of one percent up to almost 32 %.…”
Section: Introductionmentioning
confidence: 99%